2017
DOI: 10.1149/ma2017-02/42/1832
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photoelectrochemical and Photocatalytic Anodic TiO2 Nanotube Layers with Additional TiO2 coating

Hanna Sopha,
Milos Krbal,
Siowoon Ng
et al.

Abstract: In this work, strong beneficial effects of thin and uniform TiO 2 coatings within TiO 2 nanotube layers for photocurrent generation and photocatalytical degradation of methylene blue are demonstrated for the first time. TiO 2 nanotube layers were coated by TiO 2 of various thicknesses (from 2.8 nm to 22 nm) using atomic layer deposition (ALD) and compared with TiO 2 nanotube layers decorated by TiO 2 nanoparticles (using established TiCl 4 treatment) and with blank (uncoated) layers. By means of photocurrent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…29 Nitrogen doping can lower the work function, encourage charge delocalization, and efficiently promote the electron-transfer capability of CQDs. 30,31 It was also reported that nitrogen doping could increase flurescence quantum yields of CQDs. 29 Owing to their photochemical properties, electrocatalytic activity, biocompatibility, and ability to reduce the work function of CQDs, the N-CQDs showed much better performance than CQDs.…”
Section: Introductionmentioning
confidence: 99%
“…29 Nitrogen doping can lower the work function, encourage charge delocalization, and efficiently promote the electron-transfer capability of CQDs. 30,31 It was also reported that nitrogen doping could increase flurescence quantum yields of CQDs. 29 Owing to their photochemical properties, electrocatalytic activity, biocompatibility, and ability to reduce the work function of CQDs, the N-CQDs showed much better performance than CQDs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Among many different applications of anodic metal oxides, particular attention is put on semiconducting nanostructures that can be used in modern energy conversion systems, like photovoltaic (PV), 18,19 photocatalytic (PC), and photoelectrochemical (PEC) devices. [20][21][22] In recent years, several strategies have been proposed to improve the semiconducting properties of anodically generated nanostructured oxides used for energy conversion. In general, they can be divided into three groups: pretreatment strategies, those connected with modifications of the anodization process itself, or post-treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…37 Considering the possible applications in photocatalysis and photoelectrochemical systems, anodically generated TiO 2 nanotubes are most often studied. [20][21][22] However, noticeable attention is also focused on the photoelectrochemical properties of porous anodic SnO x layers because of their promising properties such as high electronic conductivity, favorable valence band edge position, as well as the possibility of self-doping. 23,29,30,38,39 Bearing in mind the enhanced photoelectrochemical activity of nanotubular TiO 2 layers with a complex internal morphology (eg, bamboo-like nanotubes 33 or branched nanotubes [40][41][42] ) and the opportunity for direct formation of a junction between two different types of anodic SnO x films, here we present for the very first time, a detailed photoelectrochemical characterization of the nanoporous tin oxide films with segments of different channel diameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium dioxide (TiO 2 ) coatings are widely used in biomedical applications and self‐cleaning coatings owing to their wear and corrosion resistance, and biocompatibility 1–4 . However, TiO 2 coatings have drawbacks, such as failure caused by bacterial infection in biomedical applications, 5 and TiO 2 photocatalytic activity is limited within the visible region owing to low sunlight absorption 6–8 . Hence, various methods have been tested to overcome this problem, including mixing with different oxides such as zirconium oxide (ZrO 2 ) and stannic oxide (SnO 2 ) to increase the photocatalytic activity of TiO 2 9,10 .…”
Section: Introductionmentioning
confidence: 99%